A RETROSPECTIVE STUDY ON ACUTE RENAL DAMAGE DURING PREGNANCY AND PUBERTY, JHARKHAND, INDIA. - Samarina Kamal (Student’s Journal of Health Research Africa, 2024)
Background Acute kidney injury is uncommon in young women while pregnant and post-delivery care, but it is linked via higher deaths and morbidity. This research aims to examine the prevalence, outcomes, and characteristics of AKI while pregnant and the post-delivery period in an Indian populace. Methods The present research examined pregnant women who were discharged from the hospital between 2022 to 2023. In expectant mothers who don’t have a history of chronic kidney disease (CKD), AKI is described as serum creatinine levels exceeding 70.72umol/l. Acute-on-CKD is defined as a fifty percent rise in creatinine levels in the serum over baseline for individuals with pre-existing CKD. Results AKI was common (0.81%) during pregnancy and postpartum. There were 172 AKI patients throughout pregnancy and postpartum, including 10 severe and 11 acute CKD cases. Haemorrhage and toxaemia caused most acute kidney injury during pregnancy and postpartum. Some 17% of women with toxaemia and 60% with HELLP syndrome develop AKI problems. Unless amniotic fluid was blocked, the pregnancy prognosis was good. Four of the seven fatalities got kidney replacement. Amniotic fluid obstruction or haemorrhage after birth killed most AKI pregnant women. Conclusion Acute renal damage a pregnant women and post-delivery care is more common than was previously thought. Toxemia is the most prevalent cause of severe kidney disease during pregnancy and post-delivery care. However, the outcome is favorable. Blockage of amniotic fluid and bleeding after delivery are the most prevalent causes of maternal death. Major Acute kidney injury may indicate an inadequate result. Recommendations To improve AKI management during pregnancy, increase regular monitoring, provide specialized training, enhance healthcare access, and promote collaborative care. Additionally, encourage further research, develop national guidelines, and ensure adequate postpartum follow-up and support.